A longitudinal study of the effects of ART on plasma chemokine levels in Malaysian HIV patients - Chew, C.S.N.; Cherry, C.L.; Kamarulzaman, A.; Yien, T.H.; Aghafar, Z.; Price, P. (2011)
Objectives: Chemokines influence the migration of leukocytes to secondary lymphoid tissue and sites of inflammation. In HIV patients, they are implicated in inflammatory complications of antiretroviral therapy (ART), notably Immune Reconstitution Disease (IRD) and Sensory Neuropathy (SN). However most chemokines have not been monitored as patients begin ART or correlated with IRD and SN. Methods: Plasma chemokine levels were assessed longitudinally using commercial ELISAs in 69 patients treated in Kuala Lumpur, Malaysia. Plasma was available at baseline and after 6, 12, 24 and 48 weeks on ART. Chemokine genotypes were assessed using allele-specific fluorescent probes. IRD were diagnosed in 15 patients. 30 patients were screened for SN using the ACTG BPNS tool after six months on ART. SN was detected in 8 patients. Results: Plasma CXCL10 levels decreased on ART compared to baseline (p = 0.002-0.0001), but remain higher than healthy controls (p <= 0.0001). The decline was clearer in patients without IRD. CCL5 levels rose on ART but remained similar to controls. CCL2 levels were higher in patients than controls after week 12. Plasma chemokine levels were not affected by CD4+ T-cell counts or any genotypes tested. Several patients with SN displayed higher CCL5 levels throughout therapy compared to patients without neuropathy. Levels of other chemokines and chemokine genotypes were not associated with SN. Conclusions: Chemokines are differentially affected by ART. CXCL10 and CCL5 may influence IRD and CCL5 warrants further investigation for an effect in SN. These trends are not influenced by chemokine genotypes investigated here.